Pengaruh Disiplin, Kompetensi Dan Kinerja Karyawan Terhadap Kepuasan Pelanggan PT.Bank Perkreditan Rakyat Shinta Daya Yogyakarta - Sulistiono; Hendrajaya; Sapto Supriyanto; Suitbertus Fajar Nugraha; JB Herimahadi; Agatha (STIE Pariwisata API Yogyakarta, 2024)
Bank Perkreditan Rakyat (BPR) is one of the formal Microfinance Institutions (LKM). From the function of human resource management (HRM), to realize BPRs can become banks that play an important role in the economic development process, one of which is through institutional strengthening, namely by improving the quality of human resources including discipline, competence, and employee performance to improve the quality of bank services to customers. and to strengthen good corporate governance (GCG). The purpose of this study was to determine the effect of discipline, competence and employee performance on customer satisfaction at PT. People's Credit Bank Shinta Daya Yogyakarta. Based on the results of data analysis, it can be concluded that: partially employee discipline has a positive and significant effect on customer satisfaction; Employee competence has a negative and significant effect on customer satisfaction; Employee performance has a positive and significant effect on customer satisfaction; and simultaneously Discipline, Competence and Employee Performance have a positive and significant effect on customer satisfaction.